PENGARUH FAKTOR PREDISPOSISI DAN FAKTOR PENDUKUNG TERHADAP KESINAMBUNGAN KEPESERTAAN JAMINAN PEMELIHARAAN KESEHATAN MASYARAKAT (JPKM) DI PUSKESMAS KALIGONDANG KABUPATEN PURBALINGGA - Arif Kurniawan; Elviera Gamelia (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2008)
Amount of participant of JKPM in Kaligondang community health center at year 2006 - 2007 experiencing of decreasing pursuant to data of Bapel JPKM and public health center, at strata of II of participant experience of decreasing from 1738 amount of participant in year 2006, becoming 1244 participant in year 2007. objective this research was tested of theory about sustainability participant of JKPM problems in Kaligondang community health center. Place of Research in Kaligondang community health center Purbalingga Regency conducted in the August - October 2008. Type of Research of observasional with method of survey having the character of analytic descriptive approach of Research used by Cross Sectional. The Population research is participant of JKPM at Kaligondang community health center of year 2007 amounting to 1247 people with research sample is 90 woman ( 36,7% ) and men ( 63,3% ). Result of this research show there is relationship having a meaning by statistic between the reached of pay for JPKM premium with continuity participant of JPKM (p-value 0,026). There is relationship having a meaning by statistic between exploiting of service of health service provider with continuity participant of JPKM (p-value 0,036). The result of this research show there is two model of influence with the independent variable to continuity participant of JPKM. First Model is influence with the reached of pay for JPKM premium (OR = 3,369) and exploiting of service health service provider (OR = 3,163) to continuity participant of JPKM. Second model is there is influence with the payment reached for JPKM premium (OR = 3,656) and promotion about JPKM (OR = 2,773) to continuity of participant of JPKM. The payment reached reached for JPKM premium is variable of most research have an effect on to continuity participant of JPKM. Suggestion in this research is Kalogondang community health center give askein or jamkesmas to society owning the payment reached of unfavourable premium and Bapel JPKM give system od appreciation or reward capable to maintain performance of cadre JPKM.